Factors Affecting on Users’ Intentions toward 4G Mobile Services in Bangladesh - Hasan, Mohammad Abid (Asian Business Review, 2019)
This study discusses the amalgamation of Technology Acceptance Model with the underlying 8 factors to investigate the intensity of users’ intentions towards 4G adoptions in Bangladesh. So, it has tried to list all the latest released facilities and the adoption tendency. A sample size of 119 respondents with random sampling as well as in-depth interviewing methods have used and collected primary data from different institutions across Bangladesh with a self-administered field survey questionnaire as well as having secondary sources from different webs, books, journals, annual reports, and unpublished research works. The SPSS and the 5-Point-Likert scale have used to validate the results. Also the tests include correlation, multiple regression technique, ANOVA, and co-efficient of variance have used. The study indicates that 36% respondents are positively prone to 4G (r2=.362, f=5.531, p=.000). Besides, among the 8 factors, the image has the greatest influence on it (β=.249, t=2.558, p=.012) followed by the variety of services (β=.189, t=1.608, p=.111), the perceived enjoyment (β=.148, t=1.803, p=0.109), the perceived ease of use (β=0.108, t=0.916, p=0.368), the personal Innovativeness (β=.098, t=.934, p=.352), and the network effects (β=.002, t=.025, p=.980). Conversely, the price (β=-.027, t=-.406, p=.685) and the perceived usefulness (β=-.069, t=-.629, p=.303) have a rare impact on it. However, with the outcomes, the telecommunication services providers will be able to accelerate the wining strategies at different levels in Bangladesh. As there are few studies published in this regard, future research is necessary to investigate the financial and industrial implications associated with it.